Large scale optimization for resource planning - Ajeet Singh (Nanyang Technological University, 2021)
With the growing demands of online shopping, keeping track of warehouse inventory is becoming a crucial component of the overall supply chain in ensuring the fast and effective delivery of goods from suppliers to consumers. In this project, we formulate it as a discrete resource allocation problem, involving manpower and automation. The idea is to use robots to automate routine tasks in the warehouse thus alleviating the manpower constraints freeing up the human resources for other more critical tasks.